BUKU CERITA RAKYAT TIMUN MAS BERBASIS TEKNOLOGI AUGMENTED REALITY (AR) UNTUK ANAK USIA GOLDEN AGE SEBAGAI LITERASI PENDUKUNG GERNAS BAKU (Science and Technology (SciTech), 2022)
Early child-reading is a stimulating activity in two stages, both cognitive and bonding. As a form of support to maximize the intellectual potential of Golden Age children in the future, the Indonesian Government through DISDIKPORA launched the National Movement - Gerakan Nasional Orang Tua Membacakan Buku (GERNAS BAKU) which is centered at the Kindergarten education level and home education with parents. The Design of a Timun Mas Folklore Book with Augmented Reality Technology is a visual-literacy support for GERNAS BAKU movement. The purpuse in this design is how to create literacy support through innovative illustrated books. The design of the Timun Mas Folklore Book for Golden Age children (2-5 years) is a combination of the Central Java’s cultural theme with Augmented Reality technology to present a modern visual appearance so that the reading experience for children is more interesting and enjoyable. The design method used is user centric based Design Thinking. The design of the AR technology illustration book considers three basic aesthetic aspects, namely appearance, content, and presentation which is adjusted to the activities of GERNAS BAKU.